Effects of welding procedure on corrosion resistance and hydrogen embrittlement of supermartensitic stainless steel deposits - Zappa Maidana, Norberto Sebastián (2013)
The effects of shielding gas and post weld heat treatment on the pitting resistance, stress corrosion cracking and hydrogen embrittlement of supermartensitic stainless steel deposits were studied. Two all-weld-metal test coupons were prepared using a metal-cored wire under Ar+5% He and Ar+18%CO2 gas shielding mixtures. Solubilizing and solubilizing plus double tempering heat treatments were done with the objective of achieving different microstructural results. The samples welded under Ar+5% He showed higher pitting corrosion resistance, for all post weld heat treatments, than those welded under Ar+18%CO2. The different post weld heat treatments generated higher susceptibility to this corrosion mechanism. None of the samples presented signs of stress corrosion cracking, but in those subjected to the heat treatment, grain boundary selective attack was observed, on the surfaces of all the samples studied. The samples with highest hardness were more susceptible to hydrogen damage, thereby leading to reduced tensile strength on this condition.